Formation pathways of mesoporous silica nanoparticles with dodecagonal tiling - Yao Sun (Nature Portfolio, 2017)
Probing the growth pathways of quasicrystalline materials, where tiling units arrange with local but no long-range order, remains challenging. Here, the authors demonstrate that dodecagonal tiling of mesoporous silica nanoparticles occurs via irreversible packing of micelles with non-uniform size distribution.